2010
DOI: 10.1002/eji.200939975
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 blockade inhibits T‐cell migration into the CNS during EAE and prevents development of adoptively transferred, but not actively induced, disease

Abstract: Autoreactive T-cell infiltration into the CNS is critical in MS and EAE. The chemokine receptor CXCR3 and its ligands are implicated in MS and mouse EAE, but the contribution of CXCR3 to T-cell migration into the inflamed CNS remains controversial. During active disease in a rat EAE model, blood T-cell, spleen T-cell and T lymphoblast migration into the CNS was inhibited by a CXCR3 blocking mAb by, 30-70%, $75% and 50-80%, respectively. However, CXCR3 blockade after active immunization did not inhibit EAE, did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
65
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 27 publications
2
65
1
Order By: Relevance
“…In EAE, both claudin-5 and occludin are downregulated, and claudin-5 has been shown to be the key determinant for BBB breakdown (39). Reductions in TJ protein levels at the impaired BBB and the influx of encephalitogenic T cells generate plaques in the brain parenchyma, resulting in the exacerbation of EAE (40). However, enhanced BBB permeability has been shown to be beneficial for RABV infection, since a permeable BBB allows immune effectors to enter the CNS and clear RABV from the CNS (7,10).…”
Section: Discussionmentioning
confidence: 99%
“…In EAE, both claudin-5 and occludin are downregulated, and claudin-5 has been shown to be the key determinant for BBB breakdown (39). Reductions in TJ protein levels at the impaired BBB and the influx of encephalitogenic T cells generate plaques in the brain parenchyma, resulting in the exacerbation of EAE (40). However, enhanced BBB permeability has been shown to be beneficial for RABV infection, since a permeable BBB allows immune effectors to enter the CNS and clear RABV from the CNS (7,10).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of differentiating Th1 cells with I-BET-762 led to down-regulated expression of the chemoattractant IP10; the leuoktriene receptors Cyslt1 and Ltb4r1; RBPj, the main transcriptional mediator of Notch signaling; and the Notch ligand Jagged. These genes are known to regulate T-cell function and the pathogenesis of numerous inflammatory models including EAE (11,14,(22)(23)(24)(25)(26). Additionally, I-BET-762 treatment also led to increased expression of genes characteristic of anergic T cells-Egr-2, IL-10, and the inhibitory cell-surface receptors Lag3, PD-1, and Tim3 (Havcr2), which are downstream targets of NFAT/Egr signaling (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore we show no CCR6 + CD8 + T cells, although all of them had infiltrated, and in this and another study we have shown that all of the CD8 + and significant proportions of CD4 + (of any cytokine subset) express CXCR3. We did not pursue the role of CXCR3 + T cells further, and studies of the role of CXCR3 + T cells in EAE continue to yield quite divergent findings (Liu et al, 2005; Muller et al, 2010; Sporici and Issekutz, 2010; Lalor and Segal, 2013). Our data does not exclude that CCR6-negative T cells had once expressed CCR6.…”
Section: Discussionmentioning
confidence: 99%